2011
DOI: 10.1002/cncr.25797
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, vitality, sleep, and neurocognitive functioning in adult survivors of childhood cancer

Abstract: Background Long-term survivors of childhood cancer are at risk for fatigue, sleep problems, and neurocognitive impairment, though the association between these outcomes has not been previously examined. Methods Outcomes were evaluated in 1426 survivors from the Childhood Cancer Survivor Study using a validated Neurocognitive Questionnaire. Relative risks for neurocognitive impairment were calculated using demographic and treatment factors, and survivors’ report on the FACIT-Fatigue, the Short Form-36 Vitalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 46 publications
4
135
4
4
Order By: Relevance
“…[64][65][66] Results from a study of adult survivors of childhood cancer showed that even many years after diagnosis and therapy, survivors are significantly more likely than siblings to report poor sleep quality and score poorer on neurocognitive functioning tests. 67 …”
Section: Disease-and Treatment-related Symptomsmentioning
confidence: 99%
“…[64][65][66] Results from a study of adult survivors of childhood cancer showed that even many years after diagnosis and therapy, survivors are significantly more likely than siblings to report poor sleep quality and score poorer on neurocognitive functioning tests. 67 …”
Section: Disease-and Treatment-related Symptomsmentioning
confidence: 99%
“…Interestingly, a substantial subset of our patients reported such symptoms with no apparent concurring clinical cause. It is therefore tempting to speculate that the number of diagnosed patients and the real number of long-term cancer survivors suffering from GH-deficiency may substantially differ due to a lack of clinical awareness (47) and that at least a proportion of symptoms categorized as 'chronic fatigue syndrome', may result from undiagnosed secondary endocrine disorders (48,49). …”
Section: Clinical Study J Gebauer E-m Fick and Others Endocrine Latementioning
confidence: 99%
“…Significant advances in the diagnosis and medical treatment of childhood cancers have drastically improved the life expectancy of children with brain tumors, and 5-year survival estimates currently range from 25 to 70 % depending on tumor location and histology [3,4]. While neurosurgery, intensive chemotherapy, and cranial radiation therapy (CRT) have substantially improved survival for these children [5,6], it is increasingly evident that the tumor and its treatments can contribute to a range of negative sequelae that adversely impact survivors' quality of life. A review by Rosen et al [2] found neurologic, neurobehavioral, and neuroendocrine complications to be common effects of cancer treatment in both the initial and long-term survival phases.…”
Section: Introductionmentioning
confidence: 99%